2018
DOI: 10.1111/jgs.15661
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Mortality in Individuals with Hip Fracture and Traumatic Brain Injury

Abstract: Importance: Mortality is significantly increased after hip fracture, with 20–30% of hip fracture patients dying within one year. Causes of the excess mortality observed in hip fracture patients are not well understood. Traumatic brain injury (TBI) sustained during hip fracture may be a cause of excess mortality in this population. Objective: To estimate the prevalence of diagnosed TBI among hospitalized hip fracture patients and examine its association with all-cause mortality. Design: Nested cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Similar to TBI, isolated spinal cord injury (SCI) was associated with reduced BMD and osteoporosis [ 145 ], predominantly observed within the trabecular metaphysical-epiphyseal areas of the distal femur and proximal tibia [ 146 , 147 , 148 , 149 ]. Further, patients suffering from SCI also frequently show HO as well as accelerated and enhanced callus formation [ 20 ], which was reproduced in vitro utilizing serum of SCI patients [ 150 , 151 ].…”
Section: Clinical Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to TBI, isolated spinal cord injury (SCI) was associated with reduced BMD and osteoporosis [ 145 ], predominantly observed within the trabecular metaphysical-epiphyseal areas of the distal femur and proximal tibia [ 146 , 147 , 148 , 149 ]. Further, patients suffering from SCI also frequently show HO as well as accelerated and enhanced callus formation [ 20 ], which was reproduced in vitro utilizing serum of SCI patients [ 150 , 151 ].…”
Section: Clinical Observationsmentioning
confidence: 99%
“…Despite the positive effect of trauma on bone regeneration, the ‘afferent’ bone-brain interaction of peripheral injury such as fracture was discovered to negatively modulate and potentially further deteriorate TBI [ 22 ]. While a neurological impact of fracture healing is considered to be constrained by the BBB, trauma patients suffering from TBI and concomitant skeletal injury show higher functional deficits and mortality rates [ 151 ]. Clinical multitrauma studies identified systemic inflammatory changes [ 152 , 153 , 154 ] with the capacity to modulate the neuroinflammatory response following TBI [ 22 ].…”
Section: Clinical Observationsmentioning
confidence: 99%
“…An additional contributor to low BMD risk in TBI patients is the use of anti-epileptic drugs, which induce the cytochrome P450 system and likely increase the conversion of vitamin D to its inactive forms, resulting in less biologically active vitamin D, decreased calcium absorption, hypocalcemia, increased PTH levels, and compensatory mobilization of calcium stores from bone (Smith et al, 2016). Polytrauma with TBI and concomitant fracture has been shown to result in higher functional deficits and mortality rates (Albrecht et al, 2019). Studies using two mouse models of TBI showed that neurological inflammation and brain damage was increased in animals with fracture and that this damage could be alleviated by blocking the inflammatory effects of fracture (Shultz et al, 2015;Yang et al, 2016).…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…Hip fracture is a very common kind of disease in clinically elderly patients. According to reports, by 2050, the number of patients with hip fractures each year around the world is about 4.5 million[ 1 , 2 ]. The incidence of hip fractures in the elderly has increased year by year, with female patients accounting for 75 % of all hip fracture patients[ 3 ].…”
Section: Introductionmentioning
confidence: 99%